Fracture and mechanical characteristics of CO2-saturated sandstone at extreme loading conditions. (May 2019) - Xing, H.Z.; Wu, G.; Dehkhoda, S.; Ranjith, P.G.; Zhang, Q.B.
Abstract: Dynamic compression and Brazilian disc tests were performed on dry, water- and brine-saturated sandstone with and without scCO2 (supercritical carbon dioxide) injection. Split Hopkinson pressure bar (SHPB) tests were conducted under different strain rates. The full-field deformation and fracturing process were investigated by the high-speed 3D digital image correlation (DIC) technique with a resolution of 256 × 256 pixels at 200, 000 frames per second (fps). The presence of CO2 attenuated the dynamic compressive strength for dry and water-saturated sandstone. The dry sandstone has a greater brittleness with the saturation of CO2, but there was an opposite trend for water-saturated sandstone saturated by CO2 . The presence of CO2 had less effect on the dynamic mechanical properties on the brine-saturated sandstone. The normalised stress threshold for crack initiation became lower for the dry and water treated specimen but was less effective in brine-saturated sandstone. The injection of CO2 intensified the fracturing degree, branching and altered the crack initiation position under dynamic loading. The mechanism of CO2 effect was studied from mineralogical structure alteration based on the observation by scanning electron microscope (SEM). Highlights: CO2 weakens dry and water saturated sandstone but less effect on sandstone saturated by brine. Strain rate enhanment effect on strength is attenuated by saturation of CO2 . CO2 makes dry sandstone brittle but ductile for water-saturated sandstone. Stress threshold for crack initiation is reduced by saturation of CO2 . CO2 alters crack initiation location and propagation path.